2011
DOI: 10.5812/kowsar.1735143x.1388
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Antibody Levels in High-Risk Health Care Workers

Abstract: Context: Hepatitis B viral infection, specially in children, is an unsolved global health issue. National and international vaccination programs, as the main means to prevent this infection, have been operating for years. This meta-analysis study was launched to investigate the vaccination efficacy in under five-year-old children in Iran. Evidence Acquisition: In this research, all national databases including, SID, Magiran, Iran medex, Iran doc, and Medlib, as well as international databases, including PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…7 Patient rights are practical measures for patient satisfaction in health care services. 8 Patient rights are an integrated component of human rights, and hence, nurses should adhere to them. Comprehensive knowledge and suitable conditions should be provided for the nurses to reduce the practice of violating patient rights.…”
Section: Introductionmentioning
confidence: 99%
“…7 Patient rights are practical measures for patient satisfaction in health care services. 8 Patient rights are an integrated component of human rights, and hence, nurses should adhere to them. Comprehensive knowledge and suitable conditions should be provided for the nurses to reduce the practice of violating patient rights.…”
Section: Introductionmentioning
confidence: 99%
“…In 6% to 10% of patients, acute hepatitis B leads to chronicity and 15% to 25% of them die from chronic liver diseases. [ 1 2 3 ] The prevalence of chronic carriers in the patients with defective immune system is higher than the general population. [ 2 ] As is hard to treat and control the chronic state, control of disease depends on prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers (HWCs) are at high risk of infection with hepatitis B virus (HBV) and hepatitis C virus (HCV) transmitted through blood and infected fluids; the infected staff can transfer these viruses to uninfected patients while providing services (2). Adib-Hajbaghery et al (1) reported that around 90% of the enrolled cases had received hepatitis B vaccination.…”
mentioning
confidence: 99%
“…According to the standard precautions for infection control, all HWCs susceptible to the infection should be identified and immunized to reduce the morbidity rate; thus the evaluation of anti-HBs antibody level is mandatory. HWCs, particularly those working in the emergency departments, operating rooms and hemodialysis centers are considered as high-risk groups (2). In addition to HBV infection, the HWCs are occupationally at the risk of HCV infection (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation